Impact of Combined Continuous Treatment on the Symptoms and Quality of Life of Children with Attention Deficit Hyperactivity Disorder: A Prospective Observational Study: Vpliv kombiniranega nadaljevalnega zdravljenja na simptomatiko in kvaliteto življenja otrok s hiperkinetično motnjo: prospektivna opazovalna študija - Venek, Saška; Gregorič Kumperščak, Hojka (Acta Medico-Biotechnica, 2021)
Purpose: Although attention deficit hyperactivity disorder (ADHD) is one of the most common neurodevelopmental disorders, studies involving the long-term treatment effects on symptoms and quality of life (QOL) are few in number and the results are conflicting. The purpose of the current study was todetermine the effect of combined (pharmacologic and non-pharmacologic) continuous treatment on the symptoms and QOL in children with ADHD after initial stabilization of symptoms.Methods: Seventeen children with ADHD (mean age = 8.5 years; 15 boys and two girls) were included in this prospective observational study. The children were assesed at baseline and 9 months later based on the ADHD Rating Scale (RS), Clinical Global Impression-Severity (CGI-S), and Child Health and Illness Profile/Parent Report Form-76 (CHIP-CE).Results: After 9 months of treatment, the ADHD RS showed improvement in symptoms in two items closely related to attention (p
Keywords: ADHD; hyperkinetic disorder; quality of life; symptoms; treatment